THE PROBLEM OF CORRELATION OF PSYCHOLOGICAL SCIENTIFIC KNOWLEDGE AND MODERN PRACTICAL METHODS OF DIAGNOSIS AND INTERVENTION - Babajanyan, I. H. (Modern Psychology, 2022)
The article is aimed at substantiate the need of taking into account the epistemological principles in the process of applying methods of psycholo- gical assessment, counseling and intervention, which in turn can contribute to the purposeful preservation of the physical and mental health of a per- son. Modern psychological assessment is an important scientific and applied component of psychological cognition. A reliable psychological assessment of individual personality traits and its mental state is of categorical impor- tance, since it is aimed at identifying a specific and situational phenomenon for the further use of various practices. In this regard, a practical psychologist must possess the professional skills of psychological diagnostics, which implies the ability to establish connections between the external signs of a phenomenon and the internal psychological characteristics of a person. In this case, a special role is assigned to the epistemological foundations of psychological science and practice, which directly affect the formation of the methodology of counseling, therapy and training.